ESTIMATING LOCAL STRAIN DUE TO COMMINUTION IN EXPERIMENTAL CATACLASTIC TEXTURES - Hadizadeh J.; Johnson W.K. (My University, 2003)
Cataclastic textures were produced by deforming porous quartz sandstone samples at room temperature, 15-200 MPa confining pressure, and 13-57% strain (γ~2-20). Particle size distribution (PSD) and fractal dimension (D) values were measured on different digital images of each sample. Over the range of applied axial strain the detectable effects of comminution (particle-size reduction through fracture) on PSD were limited to the population of particles >=7 μm. Textural variable ψ, named comminution intensity, is defined in terms of total sectional area of particle population greater than a critical size Sc. For the Massillon sandstone the Sc is close to four times the suggested value for quartz grinding limit. The comminution intensity vs. axial strain data due to the entire range of applied pressure and strain fits a power function of the form ε11=ψm, with 0.25=<m=<0.5. The local strain due to constrained comminution is then predictable by model function εL=ψn, where n=1/m, with empirical n=2.97 for the studied sandstone. The model predicts relatively monotonous textures for very small and very large strains, while the highest variety of particle size occurs at between 2 and 13% strain. Applications of the method include millimeter to meter scale mapping of the relative degree of comminution in natural fault gouge and the local strain values in experimental samples.
Keywords: LOCAL STRAIN; CATACLASTIC TEXTURES; POROUS QUARTZ SANDSTONE